Strategi branding Sekolah di era digital dalam meningkatkan animo masyarakat melalui pemanfaatan digital marketing - Wahyunto, Muh; Hidayati, Dian; Sukirman, Sukirman (Academy of Education Journal, 2024)
In the business world, schools can be considered as a brand or a trademark. A well-crafted brand will attract the interest of parents to enroll their children in that school. To ensure that the brand reaches the school's target audience, it is necessary to leverage the rapid technological developments in the era of Industry 4.0. One characteristic of the Industry 4.0 era is the growth of digital marketing. Digital marketing involves the use of digital technology to create channels for potential recipients, with the goal of effectively achieving business objectives and satisfying customer needs. This research aims to outline school branding strategies, starting from preschool (TK), elementary school (SD), junior high school (SMP), senior high school (SMA), to vocational high school (SMK). The research employs a literature study or library research method.From the analysis and discussion, the results show that school branding strategies in the digital era to enhance community interest are as follows: 1) conducting a SWOT analysis of the school, 2) establishing a competent public relations team proficient in both print and electronic media as well as social media, 3) improving academic and non-academic achievements, 4) developing social media presence including the school's website, Facebook, Instagram, and TikTok, 5) implementing Word of Mouth (WOM) strategies involving all teachers, staff, and parents, 6) maximizing the accreditation value of expertise programs and schools with an A rating, 7) enhancing the quality of teachers and teaching according to their expertise, 8) realizing the quality of graduates' character or behavior, 9) creating flagship activities that differentiate the school from others, 10) establishing a brand personality through the portrayal of a well-known figure.